THE EFFECT OF LIQUIDITY, COMPANY SIZE, AND COMPANY VALUE ON FINANCIAL DISTRESS WITH MANAGERIAL OWNERSHIP AS A MODERATING VARIABLE IN PROPERTY COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Muslikhin Muslikhin; Rusdiah Iskandar; Wirasmi Wardhani (Jurnal Ekonomi, 2023)
The researcher took the title "The Influence of Company Size Liquidity and Firm Value on Financial Distress with Managerial Ownership as a Moderating Variable in Property Companies Listed on the Indonesian Stock Exchange". This research design uses quantitative and qualitative data types in the form of secondary data obtained by accessing the website www.idx.co.id and some using data from ICMD (Indonesian Capital Market Directory). The formulation of the problem generates six hypotheses using five variables. The five variables are liquidity, firm size, firm value, financial distress and managerial ownership. This research is a quantitative and descriptive research. This research was conducted by collecting secondary data available on the Indonesia Stock Exchange during the 2021-2022 period with a total sample of 36 companies. The analytical method used is SPSS. The findings in this study indicate that the independent variable has a positive and significant effect on the dependent variable, while the contribution of the moderating variable weakens the relationship. The causes of financial distress include poor business planning, whether in terms of marketing, production, distribution or finance; the second cause is problematic cash flow where basically the influence of financial ratios on financial distress is very large.